2021
DOI: 10.1038/s41467-021-24966-0
|View full text |Cite
|
Sign up to set email alerts
|

Valence band engineering of GaAsBi for low noise avalanche photodiodes

Abstract: Avalanche Photodiodes (APDs) are key semiconductor components that amplify weak optical signals via the impact ionization process, but this process’ stochastic nature introduces ‘excess’ noise, limiting the useful signal to noise ratio (or sensitivity) that is practically achievable. The APD material’s electron and hole ionization coefficients (α and β respectively) are critical parameters in this regard, with very disparate values of α and β necessary to minimize this excess noise. Here, the analysis of thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The mechanism responsible for the low excess noise in some of these Sb containing alloys may be due in part to the large size of the Sb atom. Recent work by Liu et al [31] on the ionization coefficients in GaAsBi alloys showed that as the Bi content increases, the band-anticrossing interaction in the valence band increases the spin-orbit splitting energy (△ so ) [31]. Holes in the heavy/light hole bands now reach the Brillouin zone edge and may not be able to scatter into the split-off band from which hole ionization is mainly initiated.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism responsible for the low excess noise in some of these Sb containing alloys may be due in part to the large size of the Sb atom. Recent work by Liu et al [31] on the ionization coefficients in GaAsBi alloys showed that as the Bi content increases, the band-anticrossing interaction in the valence band increases the spin-orbit splitting energy (△ so ) [31]. Holes in the heavy/light hole bands now reach the Brillouin zone edge and may not be able to scatter into the split-off band from which hole ionization is mainly initiated.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Liu et al reported on the avalanche multiplication properties of a series of GaAsBi p-i-n and n-i-p diodes of various Bi contents and thicknesses. [38] They found that the enhanced spin-orbit splitting of GaAsBi prevented holes from accessing the split-off band and attaining the energies necessary to initiate impact ionisation. The result was that the hole ionisation coefficient in GaAsBi dropped dramatically with increasing Bi content, while the electron ionisation coefficient was left almost unaltered.…”
Section: Detectorsmentioning
confidence: 99%
“…[1][2][3] While band structure engineering has been proven to be the most powerful strategy to control charge-transfer characteristics in semiconductor devices. [4][5][6] Typically, the common approach to adjusting the band structure of materials is often carried out in the synthesis stage by varying the chemical doping, [7,8] controlling the composition of alloys (binary, ternary, or quaternary), [9,10] or constructing heterojunctions. [11][12][13] Alternatively, band structure engineering can also be realized by externally modulating in the postsynthesis stage by changing the surrounding environment including introducing a strong electrical/optical/magnetic field, [14][15][16] applying stress-strain strategies to tune crystal sizes/shapes, [17][18][19] or surface decoration and optimization.…”
Section: Introductionmentioning
confidence: 99%